Research of the role of the merchants in the development of private insurance in the Russian province on the materials of Vologda governorate in the second third of the 19th century - Lejman, Irina I. (Journal of the Belarusian State University. History, 2023)
The article deals with the formation of the system of joint-stock insurance in the Russian Empire in the second third of the 19th century on the example of the Vologda province, as well as the role of local merchants in this process. Joint-stock insurance in the Russian Empire dates back to 1827. However, it began to develop especially actively in the 1840s. The main directions in the period under review were fire insurance, transport insurance, life insurance. Based on the analysis of ads published in the newspaper «Vologodskie gubernskie vedomosti» from 1838 to 1860, a general picture of the insurance services market in the Vologda province was formed. Most of the ads were devoted to fire insurance, followed by transport insurance in popularity, then life insurance. The authorised agents together represented almost the full range of insurance companies operating at that time in the Russian Empire. The bulk of the ads were published on behalf of insurance agents from the merchant class. At the same time, transport insurance and life insurance in the Vologda province were exclusively under the jurisdiction of authorised agents from among merchants.
Keywords: merchants; Russia; newspaper «Vologodskie gubernskie vedomosti»; insurance; insurance company